Diversity and Distribution of Helminths in Wild Ruminants of the Russian Arctic: Reindeer (Rangifer tarandus), Muskoxen (Ovibos moschatus), and Snow Sheep (Ovis nivicola) - Olga A. Loginova; Sofya B. Rozenfeld; Taras P. Sipko; Ivan A. Mizin; Danila V. Panchenko; Kasim A. Laishev; Mikhail G. Bondar; Leonid A. Kolpashchikov; Aleksandr R. Gruzdev; Pavel S. Kulemeev; Dennis I. Litovka; Mariia N. Semerikova; et al. (Diversity, 2023)
The Russian Arctic supports wild sympatric ruminants and their data-deficient helminths. In this study, we: (1) collected fecal samples of wild and semiwild reindeer (Rangifer tarandus), muskoxen (Ovibos moschatus), and snow sheep (Ovis nivicola) across Palearctic North territories: Arkhangelsk Oblast (including Novaya Zemlya archipelago), Karelia and Sakha Republics, Kola, Yamal, Taimyr, and Chukotka Peninsulas, Bering, Svalbard, and Wrangel Islands; (2) conducted a coprological survey (noninvasive life-time method preferable for protected animals) to obtain eggs and larvae of helminths inhabiting digestive, respiratory, nervous, and muscular systems; (3) identified helminths according to their morphology and DNA sequences; (4) estimated parasite load per host; (5) analyzed our findings. Varestrongylus eleguneniensis (in reindeer) was reported for the Palearctic for the first time, while Orthostrongylus sp. was reported both for R. tarandus and for the Palearctic for the first time. Capillarid-type eggs were reported for snow sheep for the first time. The question of the role of wild Arctic ruminants as vectors for rotifers was raised.